"I have nine specialists. They need to swap notes!" Australian patients' perspectives of medication‐related problems following discharge from hospital. (17th March 2017) - Eassey, Daniela; McLachlan, Andrew J.; Brien, Jo‐anne; Krass, Ines; Smith, Lorraine
Abstract: Background: Research has shown that patients are most susceptible to medication‐related problems (MRPs) when transitioning from hospital to home. Currently, the literature in this area focuses on interventions, which are mainly orientated around the perspective of the health‐care professional and do not take into account patient perspectives and experiences. Objective: To capture the experiences and perceptions of Australian patients regarding MRPs following discharge from hospital. Design: A cross‐sectional study was conducted using a questionnaire collecting quantitative and qualitative data. Thematic analysis was conducted of the qualitative data. Setting and participants: Survey participants were recruited through The Digital Edge, an online market research company. Five hundred and six participants completed the survey. Results: A total of 174 participants self‐reported MRPs. Two concepts and seven subthemes emerged from the analysis. The first concept was types of MRPs and patient experiences. Three themes were identified: unwanted effects from medicines, confusion about medicines and unrecognized medicines. The second concept was patient engagement in medication management, of which four themes emerged: informing patients, patient engagement, communication amongst health‐care professionals and conflicting advice. Discussion and conclusion: This study provides an important insight into patients' experiences and perceptions of MRPs following discharge from hospital. Future direction for practice and research should look into implementing patient‐centred care at the time of hospital discharge to ensure the provision of clear and consistent information, and developing ways to support and empower patients to ensure a smooth transition post‐discharge from hospital.